Pengembangan Modul Kimia Berbasis Problem Based Learning pada Materi Minyak Bumi di SMAN 2 Mataram - Amryani, Ulyl; Muti’ah, Muti’ah; Burhanuddin, Burhanuddin; Siahaan, Jeckson (Chemistry Education Practice, 2024)
This study aims to develop a chemical problem-based learning module on petroleum material at SMAN 2 Mataram by using validity and practicality tests. The research model used is the 4D model, namely define, design, development, and dissemination. This study used a purposive sampling technique in sampling, involving 36 students of class XI MIPA 8 at SMAN 2 Mataram who were then used as respondents in a practicality test. Data analysis shows a good level of validity, with an Aiken V index of 0.88. Meanwhile, the practicality module was analyzed using the practicality index (student and teacher response questionnaire) so that the practicality module proportions were 86% (students) and 94% (teachers). These results provide evidence that the problem-based learning chemistry module on petroleum material is valid and practical. Therefore, this module can be applied in the learning process at SMAN 2 Mataram and maybe also in other schools that have a similar curriculum